MUTAGENIC EFFECTS OF SODIUM AZIDE ON THE GERMINATION IN RICE (Oryza sativa L. cv. INPAGO UNSOED 1) - Bagus Herwibawa; Florentina Kusmiyati (Jurnal Agroteknologi, 2017)
The available natural diversity highly limits the effort to improve the production of upland-rice with delicious and aromatic flavors. However, the mutagenesis can help improving the natural diversity. The aromatic-upland rice seeds, cv. Inpago Unsoed 1, were soaked in solution of NaN3 with the doses of 0 mM, 1 mM, 2 mM, 3 mM, 4 mM, 5 mM, 6 mM, 7 mM, 8 mM, 9 mM, and 10 mM, in four replications in completely randomized design. The observation included LD50, germination percentage at first-count and final-count. Data were tabulated and analyzed with CurveExpert 1.4 software for LD50, and generalized linear model in the PROC-GLM procedure of SAS 9.1 software. The means were generated and compared through Dunnett option, at probability level of 5%, in order to determine the difference in means between mutated and non-mutated seeds. The results show that the attributes of rice physiology affected by mutagenesis are sensitivity of rice to NaN3 with LD50 at 8.84 mM, and significant effect of NaN3 on the decreasing capacity of seed germination at > 6 mM for first count, and > 7 mM for final count.Keywords: germination, inpago unsoed 1, median lethal dose, rice, sodium azide